Isolation, characterization, and genomic analysis of a lytic bacteriophage, PQ43W, with the potential of controlling bacterial wilt - Huang, Binbin; Ge, Long; Xiang, Dong; Tan, Ge; Liu, Lijia; Yang, Lei; Jing, Yongfeng; Liu, Qingshu; Chen, Wu; Li, Ye; He, Haoxin; Sun, Huzhi; et al. (Frontiers in Microbiology, 2024)
Bacterial wilt (BW) is a devastating plant disease caused by the soil-borne bacterium Ralstonia solanacearum species complex (Rssc). Numerous efforts have been exerted to control BW, but effective, economical, and environmentally friendly approaches are still not available. Bacteriophages are a promising resource for the control of bacterial diseases, including BW. So, in this study, a crop BW pathogen of lytic bacteriophage was isolated and named PQ43W. Biological characterization revealed PQ43W had a short latent period of 15 min, 74 PFU/cell of brust sizes, and good stability at a wide range temperatures and pH but a weak resistance against UV radiation. Sequencing revealed phage PQ43W contained a circular double-stranded DNA genome of 47,156 bp with 65 predicted open reading frames (ORFs) and genome annotation showed good environmental security for the PQ43W that no tRNA, antibiotic resistance, or virulence genes contained. Taxonomic classification showed PQ43W belongs to a novel genus of subfamily Kantovirinae under Caudoviricetes. Subsequently, a dose of PQ43W for phage therapy in controlling crop BW was determined: 108 PFU*20 mL per plant with non-invasive irrigation root application twice by pot experiment. Finally, a field experiment of PQ43W showed a significantly better control effect in crop BW than the conventional bactericide Zhongshengmycin. Therefore, bacteriophage PQ43W is an effective bio-control resource for controlling BW diseases, especially for crop cultivation.